Proceedings of the 5th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2019) 2020
DOI: 10.2991/assehr.k.200120.032
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Well-Being and Mental Health of Students in Indonesia

Abstract: Mental health is very important in human life, especially for students studying at university. This is because problems with mental health can lead to mental disorder or emotional distress, such as depression or anxiety or psychological disfunction. Spiritual well-being can affect mental health in students. Interpersonal relationships with the environment, social, groups and God are part of the process of spiritual well-being. Therefore, this study aims to show that there is a relationship and influence of spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
(9 reference statements)
0
9
0
1
Order By: Relevance
“…Furthermore, gratitude therapy conducted for at least one week positively impacted happiness, well-being and life satisfaction (Froh et al, 2011;Lomas et al, 2014). This study is supported by the concept of psychology positive and religion (Bosacki et al, 2018;Schaefer et al, 2018), in that religious activity can be used as therapy for increasing gratitude, optimistic hope, and life well-being (Hamka et al, 2020), and positive emotions (Jin et al, 2018). Gratitude increases positive emotions, brings about life satisfaction, improves social relationships, and creates a positive environment.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, gratitude therapy conducted for at least one week positively impacted happiness, well-being and life satisfaction (Froh et al, 2011;Lomas et al, 2014). This study is supported by the concept of psychology positive and religion (Bosacki et al, 2018;Schaefer et al, 2018), in that religious activity can be used as therapy for increasing gratitude, optimistic hope, and life well-being (Hamka et al, 2020), and positive emotions (Jin et al, 2018). Gratitude increases positive emotions, brings about life satisfaction, improves social relationships, and creates a positive environment.…”
Section: Discussionmentioning
confidence: 57%
“…However, persistent anxiety aggravates mental health status and leads to serious ailments such as depression, social disorder, behavior disorders. 39 Therefore. Highly spiritual people have low levels of depression and good physical and mental health, including psychosocial aspects.…”
Section: Discussionmentioning
confidence: 95%
“…Hamka, Ni'matuzahroh, Suen 45 designed the spiritual well-being scale in Indonesia with Cronbach Alpha = 0.90. It was also developed as a general indicator of subjective well-being and perceived living standards by Ellison (2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the search result using the Google Scholar database, twelve article were found that were considered to be in accordance with the research that was raised, namely about the influenced factors of spiritual well-being. The twelve article will be described in Table 1 1, it can be seen that spiritual well-being is influenced by several factors, including: mental health (Hamka et al, 2019), spiritual coping (Sadeghi et al, 2018), life satisfaction Mathad et al, al., 2019;Alorani & Alradaydeh, 2018;Baykay, 2022), hope (Yangoobzadeh et al, 2018, primary emotions (Hebler-Ragger, 2018), mindfulness (Mathad et al, 2019), selfcompassion (Mathad et al, 2019), perceived social support (Alorani & Alradaydeh, 2018), quality of life (Ayik et al, 2019), adjustment to diseases (Ayik et al, 2019),…”
Section: Resultsmentioning
confidence: 99%